TRADITIONAL KNOWLEDGE DALAM SISTEM HUKUM HAK KEKAYAAN INTELEKTUAL INDONESIA - Syarifa Mahila (Jurnal LEX SPECIALIS, 2010)
AbstractIndonesia is a country that has a wealth of biological resources (biodiversity), the second largest after Brazil and2 a wealth of traditional knowledge in the field of medicine that is very diverse. Indonesia's traditional knowledge is developed continuously and is guaranteed if the legal protection it will have a very high economic value, which would certainly boost the economy in Indonesia. This has become a very good opportunity for Indonesia to exploit the potential value of traditional knowledge which has been shown through various processes misappropriation (misuse) by the foreign companies. Traditional knowledge is knowledge developed by indigenous peoples based on tradition or intellectual work. This knowledge includes the methods of cultivation and processing plants, medicine, art, and food-beverage recipes. protection of traditional knowledge is important because it is a source of knowledge related to human life that can be commercialized. One of the important issues relating to intellectual property rights (IPR) today is about the extent to which traditional knowledge is protected. Traditional knowledge has emerged as a new legal problem caused no domestic legal instruments capable of providing an optimal legal protection of traditional knowledge that is currently widely used by parties who are not responsible.